2016
DOI: 10.1111/jam.12998
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential of a peptide isolated from an endophyticAspergillus awamori

Abstract: The inhibitor obtained in this study possesses dual (alpha glucosidase and alpha amylase) inhibitory activity, low IC50 values, is highly stable under extreme conditions of pH and temperature, and is nonmutagenic in nature. By virtue of its properties it can be commercially produced and exploited for better management of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 35 publications
0
45
1
2
Order By: Relevance
“…Fungi (initially thought to be exclusively aerobic microorganisms) could however modify host-microbial responses in intestinal diseases due to their production of mycotoxins, especially if certain strains were capable of colonizing the anaerobic intestinal tract (e.g., as it commonly occurs in the forestomach of ruminants). In addition, A. sydowii could modify host-microbial responses in the gut in the presence of other commensal flora via epigenetic modifiers that alter the production of novel anti-inflammatory (sesquiterpenoid) molecules [21, 22]. If Aspergillus was capable of colonizing the anaerobic gut, it could modulate the microbiota and intestinal inflammation by the production of secretory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi (initially thought to be exclusively aerobic microorganisms) could however modify host-microbial responses in intestinal diseases due to their production of mycotoxins, especially if certain strains were capable of colonizing the anaerobic intestinal tract (e.g., as it commonly occurs in the forestomach of ruminants). In addition, A. sydowii could modify host-microbial responses in the gut in the presence of other commensal flora via epigenetic modifiers that alter the production of novel anti-inflammatory (sesquiterpenoid) molecules [21, 22]. If Aspergillus was capable of colonizing the anaerobic gut, it could modulate the microbiota and intestinal inflammation by the production of secretory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…() reported isolation of an α‐amylase inhibitory peptide from albumin with even higher inhibitory activity, KLPGF, with an IC 50 of 120.0 ± 4.0 μ m . Singh & Kaur () separated a peptide from endophytic fungi of Acacia nilotica, with inhibitory activity against both α‐glucosidase and α‐amylase, with low IC 50 values (3.75 and 5.625 μg/mL respectively), high stability under extreme pH and temperature and little natural mutagenicity. The inhibitor had an approximate molecular mass of 22 kDa and contained amino acids such as serine, threonine, tyrosine and valine.…”
Section: Peptides With Anti‐diabetic Propertiesmentioning
confidence: 99%
“…Three peptide fractions were obtained according to molecular size distribution, fraction I, II, and III were eluted. of Andrias davidianus could have bioactive peptide inhibiting α-amylase activity together with αglucosidase activity since these amino acid are associated with regulation and secretion of insulin.- [13,38,39] These amino acids, under suitable state enhance insulin secretion from primary islet cell and β cell lines. [40] The study reports revealed that amino acids such as leucine and arginine may play a critical role in enhancing insulin secretion by allosteric activation of metabolism or membrane depolarization, or a combination of these possibilities.…”
Section: Amino Acid Profilementioning
confidence: 99%
“…[6] Food derived bioactive peptides as natural materials are adequate for inhibiting α-amylase and αglucosidase satisfactorily with more other additional effects including antihypertensive, antioxidant, anti-microbial and anti-proliferative. [10][11][12][13][14][15][16] Enzyme hydrolysis is the promising technique in the production of bioactive peptide with higher activities compared to its precursors. Many studies underlying the beneficial and mechanism of the bioactive peptide in type 2 diabetes prevention have been elucidated.…”
Section: Introductionmentioning
confidence: 99%